BRILLIANT BLUE G DOUBLE STAINING ENHANCES SUCCESSFUL INTERNAL LIMITING MEMBRANE PEELING WITH MINIMAL ADVERSE EFFECT BY LOW CELLULAR PERMEABILITY INTO LIVE CELLS. Issue 2 (February 2015) - Hisatomi, Toshio; Notomi, Shoji; Tachibana, Takashi; Oishi, Seiichiro; Asato, Ryo; Yamashita, Takehiro; Murakami, Yusuke; Ikeda, Yasuhiro; Enaida, Hiroshi; Sakamoto, Taiji; Ishibashi, Tatsuro
Abstract : Purpose: Brilliant Blue G is used as a surgical adjuvant for retinal surgery. Although BBG double or multiple staining was reported, the effectiveness and safety of repeated staining is still elusive. To further examine the effectiveness and safety, we examined BBG in clinical cases in vivo, primary cell culture in vitro, and surgically resected specimen ex vivo. Methods: A retrospective interventional case series with in vitro and ex vivo studies were performed. Vitrectomy was performed in 28 cases of epiretinal membrane with BBG single to multiple staining. The surgically resected membranes were stained by BBG with or without cellular fixation. Primary cell cultures were examined with BBG and live/death cell markers, such as Calcein AM and TUNEL. Results: Single staining provided satisfactory staining in seven cases. Double or multiple staining substantially visualized internal limiting membrane (21 cases), especially the edges of remaining internal limiting membrane (11 cases). Adverse retinal staining was not noted and the final visual acuity showed no difference with multiple staining. The live cells barely stained with BBG, while some dead cells were stained. Conclusion: Brilliant Blue G multiple staining substantially enhanced the visualization of internal limiting membrane. The absence of abnormal staining supports the safety of repeated BBG staining. Abstract : The effectiveness and safety of Brilliant Blue G (BBG) double or multiple staining was examined in clinical cases in vivo, primary cell culture in vitro, and surgically resected specimen ex vivo. Brilliant Blue G double staining substantially enhanced visualization of internal limiting membrane without adverse staining, supporting the effectiveness and safety of repeated BBG staining.